Comparative Study of Problem-Based Learning and Traditional Teaching Methods on Medical Students’ Outcomes in Pediatrics Clerkships - Ba H; Xu L; Gu Y; Li Y; Jiang X; Li X; Li S (Advances in Medical Education and Practice)
Hongjun Ba,* Lingling Xu,* Yufen Gu, Yijuan Li, Xiaoyun Jiang, Xiaoyu Li, Shujuan Li Department of Pediatrics, First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Li, Email lixiaoyu@mail.sysu.edu.cn Shujuan Li, Email lishuj2@mail.sysu.edu.cnBackground: Problem-Based Learning (PBL) is an engaging, student-centered teaching approach that has become increasingly popular in the field of medical education. Particularly during clinical rotations, PBL is thought to enhance students’ clinical reasoning and skills. However, the impact of PBL in pediatric clerkships has not been fully explored.Objective: This study aimed to assess the influence of PBL on the clinical skills of medical interns during pediatric rotations, comparing the outcomes between PBL and traditional teaching methods.Methods: A randomized controlled trial was conducted with 72 medical interns (38 male, 34 female) participating in pediatric rotations at our hospital between November 2023 and September 2024. The interns were assigned at random to either the PBL group (36 students) or the traditional teaching group (36 students), with stratification based on baseline clinical examination scores. Both groups participated in a two-week pediatric internship, encountering identical clinical cases. The PBL group received instruction supplemented with PBL, while the traditional group received bedside teaching. The outcomes were evaluated using a theoretical knowledge exam, Mini-CEX assessments, and a PBL group satisfaction survey.Results: The results of the theoretical knowledge exam showed no significant difference between the groups (PBL group: 90.25 ± 2.15, traditional group: 89.78 ± 2.14, p > 0.05), indicating similar support for theoretical learning. Mini-CEX evaluations demonstrated that the PBL group showed significant improvements in history taking, medical decision-making, physician-patient interactions, and comprehensive clinical skills compared to the traditional group. Feedback from the PBL group was overwhelmingly positive, with students highlighting significant improvements in clinical reasoning and diagnostic skills.Conclusion: PBL significantly enhanced clinical skills in pediatric clerkships, particularly in clinical reasoning, diagnosis, and communication. Although both teaching methods supported theoretical learning equally, PBL fostered greater student engagement and deeper learning, suggesting that it could be a valuable model for future medical education.Keywords: pediatrics, teaching methods, problem-based learning, clinical clerkship